2021
DOI: 10.1016/j.metop.2021.100111
|View full text |Cite
|
Sign up to set email alerts
|

Saffron for “toning down” COVID-19-related cytokine storm: Hype or hope? A mini-review of current evidence

Abstract: Aim To assess the potential role of saffron in downregulating inflammation and cytokine storm during COVID-19. Main findings Three main compounds of saffron, i.e., crocetin esters, picrocrocin, and safranal, present strong antioxidant and anti-inflammatory action for several disease states (e.g., Alzheimer's, cancer, and depression) but have also been studied in COVID-19. In particular, based on our comprehensive review of both in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Although it is principally used as a natural dye and as a flavoring in culinary preparations, several pharmacological properties, including antioxidant, antiinflammatory, antidepressant and anticancer, have been confirmed for saffron [3]. In a very recent study, saffron has been also indicated as a promising anti-inflammatory and antiviral herbal medicine in the prevention of severe COVID-19 symptoms [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is principally used as a natural dye and as a flavoring in culinary preparations, several pharmacological properties, including antioxidant, antiinflammatory, antidepressant and anticancer, have been confirmed for saffron [3]. In a very recent study, saffron has been also indicated as a promising anti-inflammatory and antiviral herbal medicine in the prevention of severe COVID-19 symptoms [4].…”
Section: Introductionmentioning
confidence: 99%
“…Its stability in these receptors was also confirmed with MD simulations. Interestingly, saffron has been suggested to be used as a drug supplement for the treatment of SARS‐CoV‐2 in the recent reviews and a commentary (Ghasemnejad‐Berenji, 2021 ; Husaini et al, 2021 ; Mentis et al, 2021 ). Furthermore, saffron was reported to exhibit antitumor and antiviral properties.…”
Section: Resultsmentioning
confidence: 99%
“…27 In traditional Persian medicine several herbs have proved their effect in alleviation of symptoms associated with common viral respiratory infections. 28 29 …”
Section: Discussionmentioning
confidence: 99%